The relation between parents’ education level and students’ performance in the PISA study - Gísladóttir, Berglind; Haraldsson, Hans; Björnsdóttir, Amalía (Menntavísindasvið Háskóla Íslands, 2020)
Factors within school are not the sole determinants of academic performance. Research has shown that social circumstances, like parents and family, peer group, leisure-time activities as well as other factors in the larger social milieu of individuals affect educational attainment (Bong, 2008; Coleman et al., 1966; Morgan & Sørensen, 1999; Sun, 1999). In this regard, research conducted in several different countries has consistently found that, of background factors, parents’ level of education is one of the strongest predictors of student achievement (Davis-Kean, 2005; Israel, Beaulieu, & Hartless, 2001; Magnuson, 2007; Sirin, 2005). Educated parents tend to have greater academic expectations and are more likely to motivate their children academically (Mullis, Rathge, & Mullis, 2003). Furthermore, children of educated parents generally have more advantages and opportunities since their parents tend to be able to provide them with more educational resources and learning opportunities, as well as being more capable of helping them with academic course work (Gutman & Eccles, 1999). In Iceland, some have argued, based on data from Iceland’s participation in the Programme for International Student Assessment (PISA), that educational equality is one of the main strengths of the Icelandic education system. Reasons include that there is less difference between schools in Iceland than in any other OECD country and that the effect of social factors, such as parents’ level of education, is almost nonexistent in the Icelandic school system (Almar M. Halldórsson, Ragnar F. Ólafsson, Óskar H. Níelsson, & Júlíus K. Björnsson, 2010; Almar M. Halldórsson, Ragnar F. Ólafsson, & Júlíus K. Björnsson, 2013; Menntamálastofnun, 2017).The PISA study is an international survey carried out triennially. Iceland has participated in the study since it was first conducted in the year 2000. The aim of the PISA study is to evaluate education systems worldwide by assessing 15-year-old students, where many are near the ...